FAKSIONALISASI DAN KONFLIK INTERNAL PARTAI PERSATUAN PEMBANGUNAN - Rizkyansyah Rizkyansyah; Ari Ganjar Herdiansah; Djayadi Hanan (Universitas Halu Oleo, 2020)
This paper aims to examine and understand the form of factionalisation and Internal Conflict of Partai Persatuan Pembangunan (PPP) in people's perception of its existence as a political party. The method uses a qualitative approach with data and information obtained through interviews and library research methods. The data and arguments built in this paper use qualitative studies, namely by gathering various scientific references and from primary and secondary sources through searching for writings related to books, journals, papers, newspapers, magazines and direct interview results with informants related to problem in this study. The results showed that the internal PPP conflict was caused by differences in the views of political elite in determining the coalition carrying the presidential candidates. This happened in the PPP in 2014 when there were differences in the nominations between Suryadharma Ali and Romahurmuziy. The conflict then led to the dualism of the leadership of the Suryadharma Ali and Romahurmuziy camps. Another factor driving conflict is the different backgrounds of cadres in the political parties. Therefore, conflict management absolutely needs a political party.